MEETING AT MIDDLE GROUND: AMERICAN QUAKER WOMEN’S TWO PALESTINIAN ENCOUNTERS - Othman, Enaya Hammad; Öney, Celal (Muhammed Mustafa KULU, 2021)
In the late nineteenth century the Palestinian town of Ramallah began receiving American missionary women who embodied their middle-class ideology of womanhood and ventured to discourse on Arab women and culture. Their conviction of the American woman as the model for other “unfortunate” women prevented these missionaries from integrating in the Palestinian cultural context. Consequently, this Americentric belief led them to construct overwhelmingly negative views of Palestinian women as oppressed, living in ignorance and degraded conditions, and of Arab culture as backward and inept. However, American women missionaries after World War I grew in their cultural and linguistic understanding of Arab culture. This change in perspective came as a result of numerous social and cultural developments in Palestine and the United States that prepared these women to establish an accommodative middle ground between them and the Palestinians, thus modifying their previous perceptions. Among these developments were the increased secularization of the Quakers’ curriculum, more cultural and linguistic training of American teachers, the significance of Palestine as the “Holy land” in missionary imagination, and most importantly the emergence of the strategy of cooperation and devolution among the different Protestant missions in Syria and Palestine after World War I. © 2021, Muhammed Mustafa KULU. All rights reserved.
ORTAK ZEMİNDE BULUŞMA: AMERİKAN QUAKER KADIN MİSYONERLERİN FİLİSTİNLİ KADINLAR İLE KARŞILAŞMALARI
Keywords: Mission; Missionary; Ottoman; Palestine; Quaker; Ramallah